Clinical presentation of celiac disease in the pediatric population - Fasano, Alessio (Gastroenterology (New York, N.Y. 1943), 2005)
Celiac disease (CD) is an immune-mediated enteropathy triggered by the ingestion of gluten-containing grains (including wheat, rye, and barley) in genetically susceptible individuals. CD is associated with HLA molecules DQ2 (90%-95%) and DQ8 (5%-10%), and in the continued presence of gluten the disease is self-perpetuating. CD is one of the most common lifelong disorders worldwide and is characterized by a variety of clinical presentations. These include the typical malabsorption syndrome (classic symptoms) and a spectrum of symptoms potentially affecting any organ or body system (nonclassic symptoms). Because CD often is atypical or even clinically silent, many cases go undiagnosed and are exposed to the risk of long-term complications. There is growing interest in the social aspects of CD because the burden of illness related to this condition is doubtless higher than previously thought.